Credit Misallocation and Economic Growth in Vietnam - Katagiri, Mitsuru (IMF Working Papers; Working Paper ;, 2019)
The legacy of non-performing loans and high opportunity cost of government financing of bank recapitalization impeded the efficiency of financial intermediation and are an important policy issue in Vietnam. This paper presents a theoretical and empirical analysis of the issue. An empirical analysis using corporate data indicates credit misallocation between state owned enterprises and private firms in Vietnam. On the theoretical side, a micro-founded banking model is embedded in a political economy setting to assess the factors determining the size of bank recapitalization and its effects on the efficiency of financial intermediation, economic growth and welfare. The analysis suggests that recapitalization depends on an array of factors, including the tightness of the government budget and the decision maker's concern for the favored sector.